CONVERGENCE CULTURE IN THE PRACTICE OF MOBILE LEGENDS: BANG-BANG GAME - Novianti, Indira; Lawanda, Ike Iswary (UI Scholars Hub, 2023)
Games in our cultures are sustained passing through dynamic changes of society and technology Online games in digital world today allow players to play together in ubiquitous, every players access the games through their mobile phones . Mobile Legends: Bang-bang, has caused a cultural convergence compared to its previous MOBA games using PC computers. The coordination which used to play in player actions filled with strategics and creativities addressing morality and self interest in strategy. Online game MLBB with its excellence in modes converges the behavior of the players more into individual players. The analysis about cultural convergence sustains by using of grounded theory method, and the method of interview and observation to seven players conducted for data collection. The results show that the convergence culture in MLBB game on individual players as agents creates a more dynamic flowing culture. The constraints during the battle amongst players trigger the making of strategies continuously on each individual in order to be able to interact to others. The flowing condition creates the sense of self-actualization on individual players. The process of learning by each individual is the sense of humanity that online MLBB game gives to human life.